Phytoextraction of chloride from a cement kiln dust (CKD) contaminated landfill with Phragmites australis. (May 2016) - McSorley, Kaitlin; Rutter, Allison; Cumming, Robert; Zeeb, Barbara A.
Highlights: First study to report on Cl − phytoextraction from cement kiln dust (CKD) landfill. Temporal study of Cl − accumulation in shoots of Phragmites australis . Considering plant biomass, maximum Cl − phytoextraction potential realized in August. Phytoextraction from CKD landfill can remove 65 ± 4 kg/km 2 of chloride per season. Remediation potentially achievable in 3–9 year timeframe at study site. Abstract: Cement kiln dust (CKD) is a globally produced by-product from cement manufacturing that is stockpiled or landfilled. Elevated concentrations of chloride pose toxic threats to plants and aquatic communities, as the anion is highly mobile in water and can leach into surrounding water sources. Re-vegetation and in situ phytoextraction of chloride from a CKD landfill in Bath, ON, Canada, was investigated with the resident invasive species Phragmites australis (haplotype M). Existing stands of P. australis were transplanted from the perimeter of the site into the highest areas of contamination (5.9 × 10 3 μg/g). Accumulation in the shoots of P. australis was quantified over one growing season by collecting samples from the site on a bi-weekly basis and analyzing for chloride. Concentrations decreased significantly from early May (24 ± 2.2 × 10 3 μg/g) until mid-June (15 ± 2.5 × 10 3 μg/g), and then remained stable from June to August. Shoot chloride accumulation was not significantly affected by water level fluctuations at the site, however elevated potassium concentrations in the soil may have contributed to uptake. Based on shoot chloride accumulation and total biomass, it was determined that phytoextraction from the CKD landfill can remove 65 ± 4 kg/km 2 of chloride per season. Based on this extraction rate, removal of chloride present in the highly contaminated top 10 cm of soil can be achieved in 3–9 years. This is the first study to apply phytotechnologies at a CKD landfill, and to successfully demonstrate in situ phytoextraction of chloride.